PENGARUH MOTIVASI INTRINSIK TERHADAP PELAKSANAAN DOKUMENTASI PROSES KEPERAWATAN DI INSTALASI RAWAT INAP RSUD PURBALINGGA - -, hartati; -, handoyo (LPPM STIKES MUHAMMADIYAH GOMBONG, 2010)
There are intrinsic and extrinsic factors influencing work performance. Nursing document is an authentic document, eligible for evaluation and serves as a legal aspect to assess nursing quality provided by hospitals to their patients. The purpose this research is to analyze the influence of intrinsic motivation factors (the work itself, opportunity to progress, appreciation of others, and responsibility) on nursing documentation. This study used cross sectional survey. The sample consists of 125 nurses selected by simple random sampling. Data were collected using questionnaire. Multiple regression method was used to analyze the data. The result of research shows that none of the intrinsic motivation factors significantly influences the dependent variable. The coefficient of determination is very high, 0.917 meaning that the model predict 91.7 percent of the cases correctly Intrinsic motivation factors not significantly influence nursing documentation at RSUD Purbalingga. Those factors, therefore, should be closely taken care in order to improve nursing documentation. Â Keywords: intrinsic motivation, nursing documentation